Symptoms of depression as reported by Norwegian adolescents on the Short Mood and Feelings Questionnaire - Lundervold, Astri J.; Breivik, Kyrre; Posserud, Maj-Britt; Stormark, Kjell Morten; Hysing, Mari (Frontiers in Psychology, 2013)
The present study investigated sex-differences in reports of depressive symptoms on a Norwegian translation of the short version of the Mood and Feelings Questionnaire (SMFQ). The sample comprised 9702 Norwegian adolescents (born 1993 to 1995, 54.9% girls), mainly attending highschool. A set of statistical analyses were run to investigate the dimensionality of the SMFQ. Girls scored significantly higher than boys on the SMFQ and used the most severe response-category far more frequently. Overall, the statistical analyses supported the essential unidimensionality of SMFQ. However, the items with the highest loadings according to the bifactor analysis, reflecting problems related to tiredness, restlessness and concentration difficulties, indicated that some of the symptoms may both be independent of and part of the symptomatology of depression. Measurement invariance analysis showed that girls scored slightly higher on some items when taking the latent variable into account; girls had a lower threshold for reporting mood problems and problems related to tiredness than boys, who showed a marginally lower threshold for reporting that no-one loved them. However, the effect on the total SMFQ score was marginal, supporting the use of the Norwegian translation of SMFQ as a continuous variable in further studies of adolescents.